IMPLEMENTASI PEMBELAJARAN IPAS PADA KURIKULUM MERDEKA DI SEKOLAH DASAR - Juwita Isna Lestari; Andhita Putri Maharani; Andistya Ravelina Putri; Muhammad Imaduddin; Arif Mahya Fanny (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of Natural and Science (IPAS) learning in the Merdeka Curriculum in grade III of SDN Plumpungrejo 1. The focus of the research includes the planning, implementation, and evaluation stages of IPAS learning on the material of energy forms. This study used a qualitative descriptive approach with a case study method. Data collection techniques were carried out through interviews, observations, and documentation. Interview were conducted with the grade III teacher as the main informant, while observations were conducted during the learning process. The results of the study indicate that the implementation of IPAS learning in the Merdeka Curriculum at SDN Plumpungrejo 1 has been running quite well. Teachers develop learning materials by adjusting learning outcimes, learning objective, and student characteristic. In this implementation, learning is carried out through discussions, questions and answer, the use of image media, and learning videos to help student understand the forms of energy in eneryday life. The use of media and technology makes student more active in asking questions, expressing opinios, and more easily understanding the material being studied. Learning evaluation is carried out comprehensively, covering aspects of knowlegde, attitudes, and skills. Teachers also provide remedial for student who experience learning difficulties and enrichment for student who have understood the material. However, there are still obstacle, namely differences in students’ levels of understanding, so teachers need to apply more varied learning strategies and adapt them to student’ needs.